2018
DOI: 10.1080/14787210.2018.1495560
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired bacterial pneumonia in adult HIV-infected patients

Abstract: Despite active antiretroviral therapy (ART), community-acquired pneumonia (CAP) remains a major cause of morbidity and mortality among human immunodeficiency virus (HIV)-infected patients and incurs high health costs. Areas covered: This article reviews the most recent publications on bacterial CAP in the HIV-infected population, focusing on epidemiology, prognostic factors, microbial etiology, therapy, and prevention. The data discussed here were mainly obtained from a non-systematic review using Medline, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 79 publications
(104 reference statements)
0
13
1
1
Order By: Relevance
“…The specific pathogenesis that may explain the association between HIV infection and the increased risk of death in patients with acute respiratory infections is not well understood. Unlike our review, studies conducted outside Africa suggested that the presence of HIV infection did not influence the clinical outcomes of people with ARTI [57][58][59][60]. This difference can be explained by the fact that people living with HIV in Africa compared to developed countries can experience more limited access to healthcare for advanced HIV disease, malnutrition, parasitic diseases, and low antiretroviral treatment coverage [57,58,60].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The specific pathogenesis that may explain the association between HIV infection and the increased risk of death in patients with acute respiratory infections is not well understood. Unlike our review, studies conducted outside Africa suggested that the presence of HIV infection did not influence the clinical outcomes of people with ARTI [57][58][59][60]. This difference can be explained by the fact that people living with HIV in Africa compared to developed countries can experience more limited access to healthcare for advanced HIV disease, malnutrition, parasitic diseases, and low antiretroviral treatment coverage [57,58,60].…”
Section: Discussioncontrasting
confidence: 57%
“…One of the most important point to curb the burden of ARTI is to early initiate antiretroviral treatment among all HIV positive people regardless of CD4 cells count and age as recommended by World Health Organization (WHO) [74]. Antiretroviral treatment has been shown to reduce the frequency of most opportunistic infections and significantly reduce HIV-related mortality, including among people with respiratory tract infections [57][58][59][60]. However, implementing this WHO guidelines remain challenging in Africa, a continent with poor human and financial resources and weak healthcare infrastructures [75].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HIV show a higher incidence of bacterial pneumonia, which is inversely proportional to CD4 T-Cell count, when compared to the general population. Thus, superimposed bacterial pneumonia with COVID-19 is a significant consideration in PLHIV [25][26][27][28][29].…”
Section: The Risk Of Superimposed Bacterial Pneumoniamentioning
confidence: 99%
“…Patients with HIV show a higher incidence of bacterial pneumonia, which is inversely proportional to the CD4 + T cell count, when compared to the general population. Thus, superimposed bacterial pneumonia with COVID-19 is a significant consideration in PLHIV [20]. We admitted that these cases we reported could not rule out HIV-related opportunistic infections due to an urgent study and limit resource, we suspected but did not confirm PJP infection.…”
Section: Discussionmentioning
confidence: 79%